Tellurene-based saturable absorber to demonstrate large-energy dissipative soliton and noise-like pulse generations - Xu, Nannan; Ma, Pengfei; Fu, Shenggui; Shang, Xinxin; Jiang, Shouzhen; Wang, Shuyun; Li, Dengwang; Zhang, Huanian (Nanophotonics (Berlin, Germany), 2020)
Two-dimensional layered monoelemental materials (Xenes) with excellent optoelectronic properties have various property-related applications, such as energy, biomedicine, and optoelectronic devices. Xenes also show excellent performance in acting as saturable absorbers (SAs) for obtaining ultrafast laser operations. Few-layer tellurene as a typical Xenens exhibits distinct optoelectronic properties and promising practical application potential, and its nonlinear optical absorption characteristics and related ultrafast modulation applications have been investigated preliminarily. However, tellurene-based SAs to demonstrate large-energy mode-locked operations, which have special applications in industrial and scientific research areas, are seldom studied. In this work, we focus on the preparation of tellurene-based SAs and explore its applications in demonstrating large-energy mode-locked operations [dissipative soliton (DS) and noise-like pulses (NLP)]. For DS operation, the maximum average output power, pulse width, and largest pulse energy are 23.61 mW, 5.87 ps, and 1.94 nJ, respectively. NLP operation with a recorded average output power of 106.6 mW and a pulse energy of 8.76 nJ is also generated, which shows significant enhancement in comparison to previously reported Xenes-based works. Our contribution reveals the great potential and capacity of tellurene-based SAs in obtaining large-energy pulse operations and further promotes the explorative investigation of Xenes-based optoelectronic devices.